Redistribution of mineral phases of incineration bottom ash by size and magnetic separation and its effects on the leaching behaviors - Yin, Ke (2022)
Size and magnetic separation of incineration bottom ash (IBA) are common for ferrous metals recovery, however, their influences on the mineral phase and the element redistribution, and subsequently the induced variation of metal leaching potential herein remain limited understanding. The lack of research in this field may misunderstand IBA performances, cause confused results for comparison among various studies, and potentially lead to biased conclusions. We herein quantitatively investigate the effects of size and magnetic separation on the IBA based on element distribution, leaching behavior, morphology, and mineralogy with statistical analysis. For preparation, sieving was performed with the original IBA (to obtain 7 size-fractions termed as OR1-7, respectively), followed by magnetic separation of each, to further yield magnetic fractions (MF1-7) to discriminate nonmagnetic fractions (NF1-7). In this study, we show that size and magnetic separation may pose significant yet different impacts on different fractions, which would affect their leaching potential concerning their respective downstream applications.